A 6-month observational study of energy, sexual desire, and body proportions in hypogonadal men treated with a testosterone 1% gel. (March 2014) - Pexman-Fieth, Claire; Behre, Hermann M.; Morales, Alvaro; Kan-Dobrosky, Natalia; Miller, Michael G.
Abstract Aims and Methods: This was a 6-month, open label, multinational, observational study in hypogonadal men treated with daily titrated dose of 50, 75, or 100 mg 1% testosterone gel (AndroGel®) in community practice. Primary outcome was effect of treatment on hypogonadal symptoms and quality of life as assessed by Aging Males' Symptoms (AMS) scale. Secondary objectives included erectile dysfunction (International Index of Erectile Function [IIEF]), fatigue (Multidimensional Fatigue Inventory [MFI]), and surrogates for body composition (waist circumference, body mass index [BMI]). Results: Seven hundred and ninety-nine of the 1053 men enrolled had follow-up data at 6 months, 81.2% had ≥1 testosterone value in the normal range during the study. Substantial and significant improvements were observed in mean AMS score (−29%), IIEF score (+115.7%), and MFI scores (−21.5%). Further beneficial effects were significant decreases in mean BMI (−0.8 kg/m2) and waist circumference (−3.3 cm). Younger age quartiles showed greater improvements in AMS, MFI, BMI, and waist circumference than older quartiles. IIEF scores, however, did not differ significantly by age category. Conclusions: Substantial improvements in hypogonadal symptoms, quality of life, fatigue, erectile dysfunction, and libido/sexual desire were observed. Adverse drug reactions were experienced by 7.5% of the safety population over the 6-month study period.